Two-step procedure for complicated appendicitis with perityphlitic abscess formation (Swiss Medical Weekly, 2017)
PRINCIPLES Optimal management of perforated appendicitis with perityphlitic phlegmon or abscess formation is controversial. The aim of the study was to assess the outcome after a two-step procedure to treat patients with perityphlitic abscess formation. METHODS We retrospectively assessed prospectively collected data from a single-centre database that included adult patients who had appendicitis and perityphlitic abscess (≥3 cm) but no generalised peritonitis, and were treated in 2007–2015. Patients underwent a two-step procedure that comprised antibiotic treatment and drainage when technically feasible (step 1) followed by interval appendectomy (step 2). We evaluated treatment modalities, complications and outcomes. RESULTS Out of a total of 1480 patients with appendicitis, 15 patients presented with perityphlitic abscess. In addition to antibiotic treatment, computed tomography-guided drainage was performed in 12 of these cases. Step 1 and 2 hospital stays were (median, range) 7 days (5–14 days) and 2 days (2–12 days), respectively. One patient’s abscess recurred after 2 months, associated with new onset appendicitis and perforation. Another patient underwent reoperation after interval appendectomy for suspected postoperative peritonitis. CONCLUSION This two-step procedure for appendicitis with appendicular abscess was highly successful (100%) with a low rate of complications (13%). In the view of a potentially increased rate of appendicular neoplasm in combination with abscess formation, the role of interval appendectomy has to be evaluated in larger trials.